New peach cultivar ‘Mechta’ developed at the Nikita Botanical Gardens - N. V. Mesyats; A. V. Smykov (Труды по прикладной ботанике, генетике и селекции)
Background. Peach is an important commercial stone fruit crop for the Crimea and Southern Russia. In 2023, the State Register for Selection Achievements Admitted for Usage included 46 peach cultivars released by the Nikita Botanical Gardens. Meanwhile, the existing assortment of this crop has a number of disadvantages. It is necessary to increase winter hardiness and frost resistance of peach cultivars for more stable fruiting, manifestation of potential productivity, and expanding their areas of cultivation to the north, as well as to increase their adaptability to drought when they are grown under arid conditions.Materials and methods. A new peach cultivar, ‘Mechta’, was bred at the Nikita Botanical Gardens. It was obtained by crossing cv. ‘Valiant’ with cv. ‘Favorita Morettini’. The authors of the cultivar were Z. N. Perfilyeva, A. V. Smykov, V. K. Smykov, and O. S. Fedorova (patent number for breeding achievement: 9016). It was tested at the Central Division of the Nikita Botanical Gardens (Yalta) using conventional techniques for fruit crop variety trials.Results and conclusion. Cv. ‘Mechta’ demonstrated high flowering vigor (scoring 4.6 points), a long flowering period (12.7 days), stable annual yield (27.9 t/ha), high frost and drought resistance, excellent taste (4.7 points), and good biochemical parameters of the fruit. It is well adapted to the agroclimatic conditions of the Crimea’s southern coast and steppe. Its susceptibility to leaf curl was low (2.1 points), and to powdery mildew above average (3.4 points). ‘Mechta’ is recommended for use in breeding practice, as a source of valuable traits, and for commercial cultivation in the peach plantations of the Crimea and Southern Russia.